Determination of the term “Government official” in the Context of the United Nations Convention against Corruption - P. Zharovska, Halyna; I. Yuschyk, Olena; M. Bodnaruk, Oleksandr; V. Husar, Lesia; H. Toma, Mariana (Revista San Gregorio, 2020)
The article deals with the problems of determining the concept of “public official” and definiteness of terms in the context of enforcement of the United Nations Convention against Corruption. The author carried out the analysis of the specified category, identified its attributes and features of the international legal enshrinement both in the text of the Convention, and in the text of other international legal acts in the field of anti-corruption, mainly of regional value . It is established that the definition of “government official” unified by the Convention makes it possible to clearly and unambiguously determine the range of subjects of corruption to which international legal influence of not only the Convention itself,